Microplastics in Freshwater: What Is the News from the World? - Alessandra Cera; Giulia Cesarini; Massimiliano Scalici (Diversity, 2020)
Plastic has become a “hot topic” for aquatic ecosystems’ conservation together with other issues such as climate change and biodiversity loss. Indeed, plastics may detrimentally affect habitats and biota. Small plastics, called microplastics, are more easily taken up by freshwater organisms, causing negative effects on growth, reproduction, predatory performance, etc. Since available information on microplastics in freshwater are fragmentary, the aim of this review is twofold: (i) to show, analyse, and discuss data on the microplastics concentration in freshwater and (ii) to provide the main polymers contaminating freshwater for management planning. A bibliographic search collected 158 studies since 2012, providing the scientific community with one of the largest data sets on microplastics in freshwater. Contamination is reported in all continents except Antarctica, but a lack of information is still present. Lentic waters are generally more contaminated than lotic waters, and waters are less contaminated than sediments, suggested to be sinks. The main contaminating polymers are polypropylene and polyethylene for sediment and water, while polyethylene and polyethylene terephthalate are mainly found in biota. Future research is encouraged (1) to achieve a standardised protocol for monitoring, (2) to identify sources and transport routes (including primary or secondary origin), and (3) to investigate trophic transfer, especially from benthic invertebrates.